Long-Term Quality of Life and Pregnancy Outcomes of Differentiated Thyroid Cancer Survivors Treated by Total Thyroidectomy and I131 during Adolescence and Young Adulthood. (8th February 2016) - Metallo, Melanie; Groza, Lelia; Brunaud, Laurent; Klein, Marc; Weryha, Georges; Feigerlova, Eva
Abstract : Introduction . Differentiated thyroid cancer (DTC) is rare and confers good prognosis. Long-term health related quality of life (HRQoL) and pregnancy outcomes are not well known in subjects treated during adolescence and young adulthood. Methods . Cross-sectional analysis of HRQoL and global self-esteem, using SF-36 and ISP-25 surveys, and of pregnancy outcomes in female survivors of DTC treated by total thyroidectomy and I 131 before age of 25 years. Results . Forty-five of 61 patients (74%) responded to the survey. Cumulative I 131 activity was ≤3.85 GBq in 18 subjects and >3.85 GBq in 27 subjects. Mean time from diagnosis was 7.6 ± 5.2 years for the group ≤ 3.85 GBq versus 16.9 ± 11.6 years for the group > 3.85 GBq (P < 0.05 ). No significant alteration in long-term HRQoL and global self-esteem was observed. Thirty pregnancies after I 131 were noted in patients from the group > 3.85 GBq and 10 in patients from the group ≤ 3.85 GBq. Frequency of miscarriages was of 17% (group > 3.85 GBq) and 10% (group ≤ 3.85 GBq) with 9 and 24 live births, respectively. No congenital malformations or first year mortality was noted. Conclusion . Long-term HRQoL, global self-esteem, and pregnancy outcomes are not affected in young female survivors of DTC.